Formation of Extracellular C(14)-C(18) 2-D-Hydroxy Fatty Acids by Species of Saccharomycopsis - Kurtzman, C. P. (1973)
Eighteen of 19 strains of Saccharomycopsis fibuligera and one of two strains of S. capsularis produced mixtures of C(14)-C(18) 2-D-hydroxy acids in liquid culture medium. The mixture of these acids showed antimicrobial activity against Vibrio tyrogenus but not against the other microorganisms tested. Candida lactosa, a recently described species, was shown to be an isolates of S. fibuligera.